2019
DOI: 10.1109/access.2019.2923747
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Knee Joint Moment by Surface Electromyography of the Antagonistic and Agonistic Muscle Pairs

Abstract: In lower-limb rehabilitation equipment, the prediction of the knee joint moment using surface electromyography signals is an important method of motion intention recognition. To improve the viability of control by human-computer interactions and to reduce the complexity of the knee joint moment prediction model, this paper presents a prediction model for knee joint moment based on artificial neural networks, in which the knee joint angle, the knee joint angular velocity, and a pair of surface electromyography … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…sEMG is the sum of the action potentials generated by the movement of muscle motor units, and its signal generation is 20-200 ms ahead of an action [9]. Since sEMG directly reflects the movement state of each muscle and can reflect the movement intentions of the human body [10], it can better establish the humanmachine cooperative closed-loop control system of rehabilitation robots. Compared with inertial sensors, sEMG has more potential to realize man-machine collaboration.…”
Section: Introductionmentioning
confidence: 99%
“…sEMG is the sum of the action potentials generated by the movement of muscle motor units, and its signal generation is 20-200 ms ahead of an action [9]. Since sEMG directly reflects the movement state of each muscle and can reflect the movement intentions of the human body [10], it can better establish the humanmachine cooperative closed-loop control system of rehabilitation robots. Compared with inertial sensors, sEMG has more potential to realize man-machine collaboration.…”
Section: Introductionmentioning
confidence: 99%
“…Since the neural network has a strong nonlinear fitting ability, it is widely used in modeling and optimization of complex nonlinear systems [12], [22], [28]. However, the sEMG signal of the lower limb has complex nonlinearity, strong coupling, and dynamic time-variation, resulting in the lack of stability of the neural network model.…”
Section: B Algorithm Designmentioning
confidence: 99%
“…In the process of the sEMG feature extraction, many researchers used the time or frequency analysis methods to extract feature vectors from sEMG signals [9][10][11][12][13]. For example, sEMG amplitude, root mean square (RMS), zerocrossing (ZC), autoregressive-coefficient, mean absolute value (MAV), fourier transform coefficient, cepstrumcoefficients, peak frequency, and median frequency analysis methods [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Results showed that the wavelet approach could predict joint moments with higher accuracy, however, the method required a high number of inputs (two ground reaction forces and eight EMG signals). Different studies reported that merging kinematics with EMG inputs can lead to better estimation accuracy in comparison to solely using EMG signals, [24]- [27].…”
Section: Introductionmentioning
confidence: 99%